2022
DOI: 10.33650/al-tanzim.v6i1.3297
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship Education Based on Islamic Work Ethic: Educational Management Review

Abstract: This study aims to understand entrepreneurship education by implementing an Islamic work ethic in the patchwork community in Pringsewu Regency. This research was conducted on the community of patchwork craftsmen in Pekon Sukamulya, Banyumas sub-district, Pringsewu Regency from 2019 to 2021 with a qualitative approach type of research was phenomenological. Data can be obtained using observation and interviews, and documentation. Researchers used data analysis techniques starting from preparing units, data categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…IWE is a multidimensional concept, with economic, moral, and social dimensions, that can link organizations' prosperity and sustainability with society's welfare (Ali & Al-Owaihan, 2008). Using a phenomenological qualitative approach, IWE is proven to improve the welfare of the patchwork community in the Pringsewu district through entrepreneurship (Supriyanto et al, 2022). A study conducted by Ali (1992) on Saudi Arabian managers found that they adhered to Islamic work standards and were generally less egocentric than managers in other countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…IWE is a multidimensional concept, with economic, moral, and social dimensions, that can link organizations' prosperity and sustainability with society's welfare (Ali & Al-Owaihan, 2008). Using a phenomenological qualitative approach, IWE is proven to improve the welfare of the patchwork community in the Pringsewu district through entrepreneurship (Supriyanto et al, 2022). A study conducted by Ali (1992) on Saudi Arabian managers found that they adhered to Islamic work standards and were generally less egocentric than managers in other countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, Muslim entrepreneurs must follow the Shari'ah, and all the organizations must follow the Shari'ah in order to keep their earning Halal, and in addition to this, all the activities of their employees have also been noticed during working hours (Ramadani, Dana, Ratten, Tahiri, & Globalization, 2015). In Islam the entrepreneur must be active, hardworking, prosperous, intelligent, honest, very experienced, have strong memory and strong will (Supriyanto, Ghazali, Yanti, & Fauzi, 2022). There are several indications of entrepreneurial activities mentioned in the Qur'an; for example, trade is included in entrepreneurial activities: "……Allah has permitted trade" (Surah Al-Baqarah verses 275).…”
Section: Entrepreneurship In the Light Of The Qur'anmentioning
confidence: 99%
“…In the regent area of Prinseu, entrepreneurship education was carried out in "patchwork" communities based on Islamic professional ethics to improve social welfare. The quality of the products produced was maintained by adjusting the prices according to the market analysis carrying out promotional activities and by providing model services for customers (Supriyanto et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Educational responsibility is an important concept and should play a more prominent role in the organizational analysis of educational institutions (Connolly et al, 2019). Supriyanto et al (2022) understood entrepreneurship education by implementing Islamic professional ethics in the "patchwork"community of Pringsewu Regency. In the regent area of Prinseu, entrepreneurship education was carried out in "patchwork" communities based on Islamic professional ethics to improve social welfare.…”
Section: Introductionmentioning
confidence: 99%